Faktor yang Berhubungan dengan Perilaku Penggunaan Full Body Harness di Proyek Pembangunan Apartemen oleh PT. X - Ratri Apsariningdyah; Afif Amir Amrullah; Terry Y.R. Pristya (Jurnal Kesehatan, 2020)
Working at height is an important component in construction work, using a Full Body Harness (FBH) to prevent the risk of falling from a height. Needs an effort to control accidents in the workplace, that is by using an FBH. This study aims To see and learn the factors related to the behavior of the workers at height in using an FBH in the apartment project of X Company. This study method Using a cross-sectional design. Using a total sampling of 65 workers. This research shows that 81,5% using an FBH. There is a correlation between knowledge (p-value=0,001), attitude (p-value=0,001), OSH training (p-value=0,001), and the availability of FBH (p-value=0,001), but there is no correlation between the level of education (p-value=1,000), and work period with the behavior of using an FBH. There is a correlation between behavior, OSH training, availability of FBH on apartment project at X Company of 2020. The worker should use their knowledge and behavior that are received from OSH training and the company must keep the availability of FBH for workers so it will support the worker's behavior in using an FBH.